irpll Ritual as Resistance and Social Control: Exploring the Contributing Aspects of Attan in the Uprising of Pashtun Youth in Pakistan: Habibullah Kakar,Dr. Barkat Shah Kakar - jan, abdullah (JPL, 2023)
Considering the anthropological question “ritual as social order and resistance” or in the words of Max Gluckman “rituals of rebellion”, this paper seeks to find out the influence of attan (Pashtun‟s cultural dance) on the Pashtun students activism and their nationalization. Focusing attan in the light of anthropological theories of ritual as “social order,” “social control,” “rebelling and reinforcing social order” and “cultural-political resistance”, this paper seeks to answer the questions like, in what kind of contexts a ritual might be used as social control and where it rises as resistance. The main argument is that traditional dance (attan) has pave the way for connecting the youth from diverse areas of Pakistan for asserting one of their prime identities that is “Pashtun Nationalism”